2012
DOI: 10.1051/0004-6361/201218904
|View full text |Cite
|
Sign up to set email alerts
|

AKARI near-infrared spectroscopy of the aromatic and aliphatic hydrocarbon emission features in the galactic superwind of M 82

Abstract: Aims. We investigate the properties of hydrocarbon grains in the galactic superwind of M 82. Methods. With AKARI, we performed near-infrared (2.5-4.5 μm) spectroscopic observations of 34 regions in M 82 including its northern and southern halos. Results. Many of the spectra show strong emission at 3.3 μm caused by polycyclic aromatic hydrocarbons (PAHs) and relatively weak features at 3.4-3.6 μm caused by aliphatic hydrocarbons. In particular, we clearly detect the PAH 3.3 μm emission and the 3.4-3.6 μm featur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 34 publications
4
44
0
Order By: Relevance
“…1 schematic view), as predicted by Jones (2012c) and Jones et al (2013), comes from the observed 3−4 μm region emission band spectra in many sources, e.g., NGC 7023 (Pilleri et al 2015), the Orion Bar (Sloan et al 1997;Verstraete et al 2001), M17 SW, NGC 2023 (Verstraete et al 2001), M 82 (Yamagishi et al 2012) and the Seyfert 1 galaxy NGC 1097 (Kondo et al 2012). Even in these energetic regions the 3.3 μm aromatic CH band always appears to be accompanied by a CH n aliphatic plateau in the 3.4−3.6 μm region.…”
Section: Introductionmentioning
confidence: 80%
“…1 schematic view), as predicted by Jones (2012c) and Jones et al (2013), comes from the observed 3−4 μm region emission band spectra in many sources, e.g., NGC 7023 (Pilleri et al 2015), the Orion Bar (Sloan et al 1997;Verstraete et al 2001), M17 SW, NGC 2023 (Verstraete et al 2001), M 82 (Yamagishi et al 2012) and the Seyfert 1 galaxy NGC 1097 (Kondo et al 2012). Even in these energetic regions the 3.3 μm aromatic CH band always appears to be accompanied by a CH n aliphatic plateau in the 3.4−3.6 μm region.…”
Section: Introductionmentioning
confidence: 80%
“…Thus, the optEC (s) (a) model then also predicts that no IR emission band spectrum, arising from hydro-carbonaceous dust, and exhibiting only a 3.28 μm aromatic CH band, in the 3 μm region will be observable in the ISM. Some evidence that seems to support this prediction, and therefore favour an a-C(:H) origin for the IR emission bands, comes from AKARI observations of the IR emission features in M 82, which show no pure aromatic CH band but only aromatic and aliphatic CH bands that always appear together, even in the very energetic superwind region (Yamagishi et al 2012). In contrast, the PAH and (surface-hydrogenated) graphitic interstellar dust models both, implicitly, allow for the possibility of a "pure" 3.28 μm aromatic CH emission band in the 3 μm region, which is apparently never observed.…”
Section: Structural Variations and Spectral Propertiesmentioning
confidence: 94%
“…This confirms the need for non-zero offset in intensity scaling because f ali = f aro . Nagata et al 1988), (e) IRAS 04296+3429 (protoplanetary nebula, Geballe et al 1992), (f) CRL 2688 (protoplanetary nebula, Geballe et al 1992), (g) HD 34700 (debris disk, Smith et al 2004), (h) M 82 (starburst galaxy, Yamagishi et al 2012), and (i) four methylated PAH molecules. Intensities calculated at B3LYP vs. MP2 with the same basis set.…”
Section: A Rationale For a Non-zero Offset In The Intensity Scaling mentioning
confidence: 99%